KIDUNG PARI: EKSPRESI KEARIFAN LOKAL PEREMPUAN RURAL JAWA UNTUK KINI DAN NANTI - Fatimah, Mutiara Dewi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
The concept of the Kidung Pari work broadly draws inspiration from the role of rural Javanese women in farming activities, starting from pre-production, farming production, post-production, to activities outside the agricultural space, such as ngliwet or cooking rice. By drawing inspiration from each detail of these activities, positive values about the attitudes and roles of Javanese women in their social environment will become apparent. Although women’s roles in these activities may appear as “rough labor,” their involvement is significant in almost every stage of farming, from the rice fields to the kitchen. Through the composition of the Kidung Pari music, it will reveal another aspect of women, who are generally known for being gentle, beautiful, emotional, and nurturing. This community empowerment project through the arts is an effort to explore the intrinsic values and local knowledge possessed by the residents, as well as the development of existing traditional art potential as a means of preservation, education, and promotion of the region’s untapped potential. The activities to be carried out in this program include collaborative practices in visual arts and performing arts, including training in Karawitan for the mothers of the Tani Makmur group in Tawangrejo Village, and the results of this training will be showcased. The Kidung Pari work is an endeavor to immortalize the story of rural Javanese women in history, culture, society, worldview, and self-reflection in Javanese society. Through the Kidung Pari work, Indonesia needs to explore and develop new values to elevate the status of rural Javanese women, making them more superior, resilient, and empowered in the present and future.